Hukm Washiyyah al-Muslim wa Shihhatuha li Ghair al-Muslim: Dirasah Muqaranah Bayna al-Fiqh al-Islami wa Qanun al-Washiyyah fi Majmu’ al-Ahkam al-Islamiyyah al-Indunisiyyah - Khoirul Amru Harahap (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2023)
The debate of Jurisprudence scholars on law and validity of the will of a Muslim to a non-Muslim in the area of harbi, musta’min, and apostate. Whether a will is valid or not depends on the fulfillment of its pillars and conditions. Although the scholars of fiqh do not stipulate the condition of